If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + 6 = 6x + 31 Reorder the terms: 6 + X = 6x + 31 Reorder the terms: 6 + X = 31 + 6x Solving 6 + X = 31 + 6x Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + X = 31 + -6 + 6x Combine like terms: 6 + -6 = 0 0 + X = 31 + -6 + 6x X = 31 + -6 + 6x Combine like terms: 31 + -6 = 25 X = 25 + 6x Simplifying X = 25 + 6x
| 2+5e=12 | | xcosy=ycosx | | -7=1+n | | y=2/3x-19 | | 10(x-9)-9(5-6x)=2(4x-1)+5(1-2x) | | 4|=/2x-1/=12 | | 16÷8/9 | | (5y+3)(4-y)=0 | | 4c-7=3c-7 | | X+23=5x+31 | | 3+11x=5x+9 | | Ln(14)=ln(x) | | -3x+9=-2(3x+3) | | 18x+33=18x+11 | | 15x-30=15x-30 | | .8x+8+.6x=57 | | F(x)=8-ln(9x) | | A=.5(18)(2) | | 5x+13=3x+33+70 | | 8j-8=64 | | 5x+13=3x+33 | | 30+y=-4 | | 5x+13=3+33 | | u^2-2u-20=0 | | (8+w)(3w+2)= | | 12x-36=12x-36 | | 2x-9=4+6x | | .1111x=2 | | -5x=4x+5 | | 2(22)2=9 | | (2*x^4)+9=0 | | 4w+8=52 |